Free ammonia-based sludge treatment reduces sludge production in the wastewater treatment process. (August 2018) - Yang, Guojing; Xu, Qiuxiang; Wang, Dongbo; Tang, Li; Xia, Jingfen; Wang, Qilin; Zeng, Guangming; Yang, Qi; Li, Xiaoming
Abstract: Excessive sludge production is one of the major challenges for biological wastewater treatment plants. This paper reports a new strategy to enhance sludge reduction from the wastewater treatment process. In this strategy, 1/5 of the sludge is withdrawn from the mainstream reactor into a side-stream unit for sludge treatment with 16 mg/L free ammonia (FA) for 24–40 h. The FA-treated sludge mixture is then returned to the mainstream reactor. To demonstrate this concept, two reactors treating synthetic domestic wastewater were operated, with one serving as the experimental reactor and the other as the control. Experimental results showed that the experimental reactor exhibited 20% lower in sludge production than the control. FA treatment effectively disintegrated a portion of extracellular or intracellular substances of sludge cells in the FA treatment unit and lowered the observed sludge yields in the mainstream reactor, which were the main reasons for the sludge reduction. Although FA treatment decreased the activities of nitrifiers, denitrifiers, and polyphosphate accumulating organisms in the FA treatment unit, this strategy did not negatively affect the reactor performance and sludge properties of the experimental reactor such as sludge settleability, organic removal, nitrogen removal and phosphorus removal. Further investigation showed that the organics released from the FA treatment process could be used by PAOs and denitrifiers for carbon sources. Graphical abstract: Image 1 Highlights: A new strategy was developed for sludge reduction from wastewater treatment process. The strategy was implemented through treating part of the sludge with FA. 16 mg N/L FA caused ∼20% of sludge reduction in the experimental reactor. Reactor performance and sludge properties were not affected by FA treatment.